2009
DOI: 10.1177/0883073808321056
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Seizures: Treatment and Treatment Variability in 31 United States Pediatric Hospitals

Abstract: Neonatal seizures are one of the most common neurological disorders in infants. However, the optimal treatment strategy for neonatal seizures remains controversial and there is little data regarding current treatment of neonatal seizures. In this study we describe the current treatment of neonatal seizures and variation in practice among 31 pediatric hospitals in the United States. We retrospectively identified 6099 infants hospitalized in the first month of life in one of 31 pediatric hospitals participating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 14 publications
0
53
1
Order By: Relevance
“…PHIS data have been used in many recent analyses of pediatric care. [11][12][13][14][15][16][17][18][19][20] Kaplan et al examined the validity of birth weight, vitamin A use, and discharge year and found that agreement was 91%, 97%, and 100%, respectively. 15 The cohort included 22 699 unique infants admitted to participating NICUs from January 1, 2007, until June 30, 2010, with a gestational age of 22 to 33 weeks and a birth weight of 400 to 3999 g. We excluded infants born at ,22 weeks' gestation and birth weight ,400 g. We excluded infants with birth weight $4000 g because this finding was most likely a clerical error given our ,34-week gestation population.…”
Section: Study Design and Datamentioning
confidence: 96%
See 1 more Smart Citation
“…PHIS data have been used in many recent analyses of pediatric care. [11][12][13][14][15][16][17][18][19][20] Kaplan et al examined the validity of birth weight, vitamin A use, and discharge year and found that agreement was 91%, 97%, and 100%, respectively. 15 The cohort included 22 699 unique infants admitted to participating NICUs from January 1, 2007, until June 30, 2010, with a gestational age of 22 to 33 weeks and a birth weight of 400 to 3999 g. We excluded infants born at ,22 weeks' gestation and birth weight ,400 g. We excluded infants with birth weight $4000 g because this finding was most likely a clerical error given our ,34-week gestation population.…”
Section: Study Design and Datamentioning
confidence: 96%
“…Nevertheless, there are substantial differences in care patterns across NICUs, similar to variability in care that has been described for other treatments. [12][13][14][15]20 The variation in care points to the importance of comparative effectiveness research to develop evidence-based treatment algorithms.…”
Section: Figurementioning
confidence: 99%
“…Surveys of physicians suggest that there is a considerable variation in practice. [3][4][5][6][7] Such variation may be related to a lack of evidence to support medication selection or to guide the optimal duration of therapy. 3,8 Importantly, studies of patient or parental opinions of seizure management for older children and adults demonstrate that their goals and priorities do not always match established medical definitions of success.…”
Section: Introductionmentioning
confidence: 99%
“…Phenobarbital is a barbiturate drug used in the treatment of different forms of paediatric epilepsy and status epilepticus (BNF for children, 2011) being the first-line choice to control neonatal seizures (Lehr et al, 2005;Blume et al, 2009;Ouvrier et al, 1982). It is also used to treat neonatal abstinence syndrome both in the case of sedative-hypnotic withdrawal and as an adjunct therapy to treat opiate withdrawal symptoms (Bio et al, 2011;Finnegan and Kandall, 2005;Osborn et al, 2010).…”
Section: Introductionmentioning
confidence: 97%